Coexisting Agency and Stewardship Governance in Family Firms: An Empirical Investigation of Individual-Level and Firm-Level Effects. (December 2017) - Madison, Kristen; Kellermanns, Franz W.; Munyon, Timothy P.
This article theoretically and empirically intertwines agency and stewardship theories to examine their distinct and combined influences on family firms. Primary matched triadic data from CEOs, family employees, and nonfamily employees in 77 family firms suggest that agency and stewardship governance affects individual-level behavior and firm-level performance. Specifically, agent behavior is highest under conditions of coexisting low agency governance and high stewardship governance and is lowest when agency and stewardship governance coexist at high levels. Furthermore, when high levels of agency and stewardship governance coexist, family firm performance is the highest. Theoretical implications and future research directions are discussed.